Computationally assisted structure elucidation of new 2-guanidinoethanesulfonyl sesquiterpenoid alkaloids: Agelasidines G–I from the marine sponge Agelas nakamurai. (5th November 2022) - Lin, You-Cheng; Chao, Chih-Hua; Fu, Chung-Wei; Chiou, Shu-Fen; Huang, Tzu-Yin; Yang, Yen-Ju; Wu, Shih-Hsiung; Chen, Shu-Li; Wang, Hui-Chun; Yu, Meng-Chen; Huang, Hui-Chi; Sheu, Jyh-Horng
Abstract: Three new 2-guanidinoethanesulfonyl sesquiterpene analogues of (−)-agelasidine A, agelasidines G–I (1 –3 ), were isolated from a marine sponge Agelas nakamurai collected in Orchid Island. The absolute configurations of agelasidines G–I (1 –3 ) were established by utilizing the computational NMR data, a statistical DP4+ method, and comparing their experimental optical rotations with the B3LYP calculated data. Moreover, an optical pure bromopyrrole alkaloid, (−)-mukanadin C (4 ), was discovered for the first time and its absolute configuration was confirmed by a single crystal X-ray diffraction analysis. These marine natural products were evaluated cytotoxic, antimicrobial, and anti-inflammatory activities. Graphical abstract: Image 1 Highlights: Three new 2-guanidinoethanesulfonyl sesquiterpenes were isolated from a marine sponge Agelas nakamurai . The DP4+ method and computational optical rotations were applied to establish the absolute configurations of 1 –3 . (−)-Mukanadin C (4 ) was discovered for the first time by a single crystal X-ray diffraction analysis.